Evaluation of the Current Knowledge About Bacterial Endocarditis Prevention Among General Dentists in the City of Santo Domingo, Dominican Republic - Aragoneses, Juan Manuel; Aragoneses, Javier; Brugal, Vanessa Arlette; Algar, Juan; Suarez, Ana (Frontiers in Public Health, 2020)
Infective endocarditis (IE) is a life-threatening disease caused by bacterial adherence to the lining of the heart and heart valve, and it can be caused by bacterial contamination of the bloodstream during invasive dental procedures. The American Heart Association (AHA) recommended guidelines for antibiotic prophylaxis in 2008 before invasive dental procedures; however, in the Dominican Republic, no official guidelines or regulations on this topic have been yet established. This study aimed to evaluate the current knowledge about bacterial endocarditis prevention among dentists in Santo Domingo. The study participants were dentists who attended a conference organized by Universidad Federico Henríquez y Carvajal (n=95), of which 74 responded to the questionnaire survey. 78% of the participants responded that an indication of antibiotics is recommended in cases of prophylaxis for IE. The prescription of antibiotics was applied to patients with prosthetic valves (78.4%), presented a history of previous IE (77%) among others. Among all the interventions in which the respondents would prescribe antibiotics, tooth extraction (70.7%) was the most frequent. Amoxicillin was the preferred drug choice (63.5%) and clindamycin was the antibiotic of choice in allergic patients (55.4%). Even though the choice of antibiotics were according to AHA guidelines (2008), majority of the dentists (58.82% and 55.4%)were not aware of the correct dosage and timing of administration of azithromycin and clindamycin in drugs in patients allergic to penicillin.